Antennal morphology and sensillar equipment vary with pollen diet specialization in Andrena bees. (July 2020) - Polidori, Carlo; Jorge, Alberto; Ornosa, Concepción
Abstract: Several studies recently reported that specialized (oligolectic) bees, which collect pollen from few host plants, use, besides visual cues, specific volatiles to find their hosts. Generalist (polylectic) bees, on the other hand, likely have to recognize a wider range of volatiles because they forage on many plant species. Bee antennal sensory equipment may thus be under selection to optimize plant host recognition. This selection may have led to variation in sensory equipment morphology with diet specialization (lecty). We tested if lecty correlates with antennal morphology and abundance of the main olfactory/gustatory sensilla (sensilla trichoidea (ST), placoidea (SP), sensilla basiconica (SB)) in the genus Andrena (Hymenoptera: Andrenidae). Across 24 species, and after having controlled for body size, we found polylectic species to have a longer and narrower flagellomer F9 (the one with highest abundance of sensilla), and to have a greater ST density on F9, compared with oligolectic species. Neither SP density nor SB number varied with lecty. A cluster analysis furthermore depicted groups of species that reasonably reflect diet specialization. Our results are in line with the previously observed lower number of glomeruli in the brain of oligolectic, compared with polylectic, bees. A formal correction for phylogeny is necessary to confirm our preliminary conclusion that pollen diet specialization has driven the morphology of the peripheral sensory system in this bee genus. Graphical abstract: Image 1 Highlights: We tested if the antennal sensory system varies with pollen specialization in Andrena bees. Polylectic species have a longer flagellomere F9 than oligolectic species. Polylectic species have a greater density of sensilla trichoidea than oligolectic species. Abundances of sensilla placoidea and sensilla basiconica did not vary with lecty. More sensilla trichoidea may serve to recognize a wider range of volatiles in polylectic species.